2021
DOI: 10.24036/00430za0002
|View full text |Cite
|
Sign up to set email alerts
|

Zoom breakout room for students’ collaborative skill enhancement in history learning during Covid-19 outbreak

Abstract: The new transformation in history learning is needed in online learning, especially when it comes to improving students’ collaborative skills in solving problems, finding solutions, making decisions, and negotiating to achieve particular goals in 21st-century learning skills. Virtual learning rooms such as Zoom are used to ensure students’ involvement and collaboration in learning and provide opportunities for students to realize active learning with many features that can be applied. Despite many studies that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…This experience is effective as it can raise a student's efficacy belief by fostering the belief that they can do the same, especially when the person performing the task is believed to have the same capabilities as they do (Mills, 2009;Pekmezi et al, 2009). The study's findings augmented the previous studies suggesting that group work in breakout rooms promotes collaborative learning activities (Agustina, 2021;Lee, 2021). This collaboration facilitates students to have the experience of speaking and, at the same time, to have the experience of observing models.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…This experience is effective as it can raise a student's efficacy belief by fostering the belief that they can do the same, especially when the person performing the task is believed to have the same capabilities as they do (Mills, 2009;Pekmezi et al, 2009). The study's findings augmented the previous studies suggesting that group work in breakout rooms promotes collaborative learning activities (Agustina, 2021;Lee, 2021). This collaboration facilitates students to have the experience of speaking and, at the same time, to have the experience of observing models.…”
Section: Discussionsupporting
confidence: 59%
“…Considering this, coupled with their reflection on the failure to have well-engaged online classes in the previous semesters due to a lack of student-student interactions, the authors, who were also serving as the lecturers of the classes, changed the online learning platform to Zoom videoconferencing application. Studies found that Zoom has become one of the most preferred online learning platforms (Agustina, 2021;Correia et al, 2020;Sakkir et al, 2020). Besides being easy to use, a feature that attracts teachers and students to using Zoom is its breakout rooms (hereafter "BRs").…”
Section: Introductionmentioning
confidence: 99%
“…For collecting the qualitative data, a semi-structured interview was performed. In formulating questions for the interview, the researchers combined Redmond et al's (2018) theory with Agustina and Suharya's (2021) statement on students' perspectives of peer-to-peer in an online method, Lee's (2021) statement that group work discussion can increase students' active participation, and Krause's (2005) statement that effective discussions can improve speaking skills.…”
Section: Methodsmentioning
confidence: 99%
“…One of Zoom's features is Breakout rooms that can be used in online teaching. In Zoom, the Breakout Rooms feature is a virtual room separate from the main room (Agustina & Suharya, 2021). The use of the Breakout rooms can be a game-changer in anticipating learning obstacles in digital learning (Lee, 2021).…”
Section: Zoom Main Room and Breakout Rooms Featurementioning
confidence: 99%
“…This seems to indicate that students are not yet familiar with math applications which can be used to facilitate such needs. Several studies underlined some factors which tend to cause that issue, namely: mathematics teachers' lack of digital literacy (Al Ghazali, 2020;Seidu & Owusu-boateng, 2022), socio-economic factors (Soesanto & Dirgantoro, 2021c), and geographical issues that are related to the advancement of infrastructure (Agustina & Suharya, 2021;Rahiem, 2021). Therefore, the findings of the current research suggest the needs for socialization and enrichments to teachers to minimize such gap, and of course to see and consider the context of Indonesia as an archipelago with different levels of digital literacy and socio-economic.…”
Section: Students' Suggestions About Ai-based Learning In Mathematics...mentioning
confidence: 99%